PENERAPAN BUSINESS INTELLIGENCE NETWORK OPERATION & QUALITY CONTROL DASHBOARD PADA PT. BAKRIE TELECOM - Sutikno, Agung (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2022)
Information systems at PT. Bakrie Telecom has been running still focused on transactional data so only the current information system is monotonous, rigid and less interactive. This condition causes stakeholders and the level of managerial can not optimally serve in managerial field because not optimal in data analysis about the state of implementation of the program. Therefore we need a Business Intelligence Software that providing information data which will be used in decision support by using Datawarehouse. Datawarehouse support for management decision by collecting and organizing data analysis and reporting for management.